MANAJEMEN STRATEGI PROGRAM GURU PENGGERAK (PGP): - Rohmad, Azzufa Nurkamila; Mulyono, Mulyono (Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
This research aims to analyze the strategic management of the Teacher Mobilization Program (PGP) as an agent for the transformation of independent curriculum learning at the Center for Teacher Mobilization (BBGP) in East Java. The Merdeka Curriculum is an innovation in the Indonesian education system by emphasizing independence, creativity, and innovation in the learning process. PGP, as the spearhead of the implementation of the Independent Curriculum, is expected to be an effective agent of change in improving the quality of learning in schools. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews, participant observation, and the analysis of related documents. The research respondents consisted of PGP managers and implementers at BBGP East Java. Data analysis techniques are carried out through data reduction, data presentation, and drawing conclusions. The research results show that the PGP strategy management at BBGP East Java has made a significant contribution to facilitating the implementation of the Merdeka Curriculum. The strategies used include training and competency development, establishing learning communities, strengthening collaborative networks, and effective resource management. In addition, managing conflict and change is an important focus of PGP strategic management to ensure program sustainability. In conclusion, PGP strategy management at BBGP East Java is a key element in the learning transformation of the Independent Curriculum. This research provides an important contribution to understanding the role of PGP as an agent of change in the Indonesian education system, as well as providing recommendations for the development of similar programs in the future. Keywords: Strategic Management, Mobilizing Teacher Program, Center for Mobilizing Teachers